Imaging and Histopathology Correlation of Solid Papillary Carcinoma of the Breast : A Review of Four Cases - MIA, Sharifah; M, Azwini; AS, Nordashima (IIUM Medical Journal Malaysia, 2015)
Solid papillary breast carcinoma is a rare type of breast carcinoma. We present four cases which highlight the radiological and histological findings of solid papillary carcinoma. Mammogram supplemented with ultrasound played an important role in detecting solid papillary carcinomas which usually presents as intraductal lesions or intracystic mass with Doppler signal. Excision biopsy is a better option than core biopsy as the latter modality may not be representative and the diagnosis of solid papillary breast carcinoma may be missed.